Luoghi da (ri)costruire. Elementi per uno studio sistematico della storia dei multiplex in Italia (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
This article explores the phenomenon of multiplex cinemas in Italy, emphasizing their historical and legislative context. Emerging in the 1990s, multiplexes represent a modern form of globalized consumption, distinct from traditional cinemas. Their rapid expansion, driven by large foreign conglomerates, posed significant challenges and opportunities within the Italian market. Through a historical reconstruction using trade magazines, this study analyzes the legislative measures enacted to regulate this growth, the involvement of various stakeholders, and the distinctive characteristics of the Italian multiplex landscape in its preliminary phase.
Keywords: multiplex; Movie theatres; media industry studies; local history; Italian press